The Innovation of Knowledge Management and Library and Information Science - Lv, Xiaohong (Journal of Theory and Practice of Social Science, 2023)
The large range of enterprise demand for innovation makes knowledge management system emerge at the historic moment. Knowledge management is the measures taken by enterprises to cope with environmental change and other problems. It aims at the internal adaptability of enterprises, so it is an adaptive measure. Knowledge management develops rapidly, because it fully ADAPTS to the three-dimensional environment of innovation and sharing new knowledge, and greatly satisfies the demand. The current knowledge management system research has been extended to the research scope of library and information science, and has produced extremely far-reaching influence.